Data sharing in transboundary water management - Sarfaraz, M. Umer; Hall, Damon M.; Rotman, Robin M. (Frontiers in Water, 2022)
Half the world’s population resides within 310 transboundary lake and river basins shared among 151 riparian nations. Approximately 60% of these basins lack cooperative frameworks to share water. The complexities of sharing water necessitate identifying approaches for managing transboundary international freshwater resources. While much has been written about the histories, theory, and mechanisms of transboundary water management, conflict, and cooperation among riparian nations, we draw attention to scholarship written about what we believe is the central tool for cooperation: data and data sharing. The 1997 United Nations’ Convention on the Law of the Non-Navigational Uses of International Watercourses (UN Watercourse Convention) recognizes sharing water resources data is vital to river basin cooperation. Data sharing builds trust between riparian states, aids in mitigating conflict, and improves environmental, economic, and social outcomes. Despite calls to increase data sharing in transboundary basins to support cooperative management, few papers review the role of data sharing in transboundary water management, including how often and what types of water resources data and information are shared. We synthesize the role of data in conflict and collaboration from peer-reviewed papers on transboundary water management from the year the UN Watercourse Convention went into force, 2014 to May 2022. We outline what scholars argue are the types of water-related data to be shared, the frequency of data sharing, and the mechanisms for sharing data for facilitating cooperation in transboundary waters.